Pemanfaatan ABC Flash Card Game dalam Meningkatkan Kesiapan Anak TK Kelompok B Masuk Sekolah Dasar - Paranita, Wira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This study aims to observe how the use of ABC Flash Cards among Group B kindergarten students at Negeri Pembina Monterado improves their readiness for primary school. Additionally, it seeks to enhance the preparedness of 20 Group B students, aged 5-6, for entering elementary school. The research was conducted in two cycles, each consisting of two meetings. Data were collected through tests and observations to improve the children's ability to recognize alphabet letters. The study employed observation rating scales and ABC Flash Card games to demonstrate mastery of letter recognition and pronunciation. In the first cycle, this percentage increased to 62.64% (good), and in the second cycle, it further improved to 82.24% (very good). Both quantitative and qualitative descriptive analysis methods were used to analyze the data. The results of the study showed that the readiness of children aged 5 to 6 for primary education improved significantly. Furthermore, the method used by the teacher to enhance the students' skills through ABC Flash Cards was novel to the children, allowing them to learn without the need for writing. The activities carried out in this research also included introducing letters that form initial syllables, along with visual aids to prevent boredom, and encouraging reading.